Explorando diferentes vias de inoculação do embrião de galinha como modelo experimental em análises de farmacocinética e toxicidade de drogas comerciais e nanoformulações lipídicas e poliméricas - Notário, Fabiana Oliveira (2025)
The chicken embryo has become an important experimental model for pharmacokinetics and toxicity analyses due to its ease of handling, serving as a promising alternative for preclinical testing. However, there is still a scientific gap regarding the standardization of toxicity and pharmacokinetics tests depending on the route of inoculation in this model. This study aimed to evaluate whether the route of inoculation alters the toxicity of commercial and nanoformulated drugs (norfloxacin, indomethacin, and lidocaine) and to verify if different routes of inoculation affect the pharmacokinetic parameters of commercial and nanoformulated norfloxacin in serum and allantoic samples from chicken embryos. For toxicity analysis, the drugs (norfloxacin, indomethacin, and lidocaine) in their commercial and nanoformulated forms were inoculated in five different doses at 10 days of development through various routes (shell membrane, allantois, chorioallantoic membrane, and amnion). At 16 days of incubation, mortality, embryo weight, and liver and kidney histological analysis were evaluated. Additionally, the presence of norfloxacin in serum and allantoic fluid after this period was assessed. Pharmacokinetic parameters were analyzed by administering a single dose of commercial and nanoformulated norfloxacin inoculated through the aforementioned routes, with samples taken from serum and allantoic fluid at 30 minutes, 1, 4, and 24 hours post-inoculation. No embryonic lethal dose 50 (LD50) was found for any drug. Norfloxacin did not significantly affect embryo weight. Commercial lidocaine caused an increase in embryonic weight, whereas its nanoformulation did not produce the same effect. Indomethacin significantly reduced embryo weight in both formulations. All histological lesions were associated with nanoformulated drugs inoculated via the amnion. Norfloxacin has caused inflammatory alterations in the kidney and degenerative changes in the liver. Lidocaine induced kidney degeneration, while indomethacin led to liver degeneration. Regarding pharmacokinetic parameters, only the time to maximum concentration and elimination constant were observed for the commercial drug. A blood maximum concentration time (Cmax) of 1 hour for norfloxacin was noted across all administration routes, except for the amnion route, which showed a Cmax 24 hours post-administration. Interestingly, the Cmax of the drug in the allantoic fluid was only detectable in embryos inoculated via the amnion. This study demonstrates differences among routes, with the amniotic route showing a pharmacokinetic distribution characterized by a typical absorption curve with a rise, peak, and decline for the allantois and serum, with a slower distribution. The drug's rapid distribution and elimination in the serum were observed for the other routes, but the allantois is not suitable for pharmacokinetic analysis. Thus, it is likely that drug biotransformation occurs in embryos inoculated at 10 days and evaluated at 11 days of incubation, with slower distribution in the amnion route, explaining the higher toxicity observed. Moreover, only via this route is it possible to assess the drug's pharmacokinetics in the allantois. Therefore, the chicken embryo can be used as a pharmacokinetic model, with particularities depending on the route of inoculation.